Species delimitation of the northeastern Anatolian Symphytum (Boraginaceae) taxa - Özgi̇şi̇ Kurtuluş; Tarikahya-Hacioğlu, Burcu (Phytotaxa, 2021)
Symphytum is regarded one of the most complicated genera in terms of the classification of its members among the Boraginaceae. In addition to different infrageneric classification methods, several species complex or aggregates have been proposed to deal with the taxonomical problem of genus members. Symphytum asperum aggregate was first introduced by Kurtto, who proposed six taxa within this aggregate. However, according to further studies by different researchers based on morphological data, total number of species of the complex was variable. The number of species was reduced to three, comprising S. asperum, S. savvalense, and S. sylvaticum, after the phylogenetic and morphological studies of Tarıkahya-Hacıoğlu and Erik. However, the taxonomical status of some of these species (i.e., S. savvalense and S. sylvaticum, and S. sepulcrale), which was assigned as a member of this complex by Kurtto, has been regarded as unresolved. To solve this uncertainty, different species delimitation methods were used, including statistical parsimony network analysis (TCS), generalized mixed Yule coalescent (GMYC), and Bayesian Phylogenetics and Phylogeography (BPP) of the ITS, trnL-F and trnS-G sequence data. In addition to members of this complex, S. ibericum, which is phylogenetically nested within the S. asperum aggregate, was also used. The TCS and GMYC analyses demonstrated more complicated clusters, whereas high posterior probabilities of BPP clusters were more compatible with the morphological data. In accordance with the morphological approach of Tarıkahya-Hacıoğlu and Erik, the species delimitation analyses based on molecular data support the recognition of S. asperum, S. ibericum, S. savvalense, and S. sylvaticum as different species.